Cord blood presepsin as a predictor of early-onset neonatal sepsis in term and preterm newborns - Francesca Priolo; Luca Maggio; Simona Fattore; Marta Tedesco; Domenico Umberto De Rose; Alessandro Perri; Giorgia Prontera; Roberto Chioma; Annamaria Sbordone; Maria Letizia Patti; Giovanni Vento (BMC, 2023)
Abstract Background To date, no studies on presepsin values in cord blood of term infants with risk factors for early-onset sepsis (EOS) are available, whereas only one study reported presepsin values in cord blood of preterm infants at risk. In this study, we investigated the presepsin values in cord blood of term and preterm infants with documented risk factors for EOS. Methods In this single-center prospective pilot study, we enrolled neonates presenting with documented risk factors for EOS. P-SEP levels were assessed in a blood sample collected from the clamped umbilical cord after the delivery in 93 neonates, using a point-of-care device. The primary outcome of our study was to evaluate the role of cord blood P-SEP in predicting clinical EOS in term and preterm infants. Results During the study period, we enrolled 93 neonates with risk factors for EOS with a gestational age ranging between 24.6 and 41.6 weeks (median 38.0). The median P-SEP value in all infants was 491 pg/ml (IQR 377 - 729). Median cord P-SEP values were significantly higher in infants with clinical sepsis (909 pg/ml, IQR 586 - 1307) rather than in infants without (467 pg/ml, IQR 369 - 635) (p = 0.010). We found a statistically significant correlation between cord P-SEP value at birth and the later diagnosis of clinical sepsis (Kendall's τ coefficient 0.222, p = 0.002). We identified the maximum Youden's Index (best cut-off point) at 579 pg/ml, corresponding to a sensitivity of 87.5% and a specificity of 71.8% in predicting clinical sepsis. Conclusions Maximum Youden's index was 579 pg/ml for clinical EOS using cord P-SEP values. This could be the starting point to realize multicenter studies, confirming the feasibility of dosing P-SEP in cord blood of infants with risk factors of EOS to discriminate those who could develop clinical sepsis and spare the inappropriate use of antibiotics.